Novel mutations of the SRF gene in Chinese sporadic conotruncal heart defect patients - Xu Mengmeng; Xu Yuejuan; Chen Sun; Lu Yanan; Li Fen; Sun Kun (BMC, 2020)
Abstract Background Conotruncal heart defects (CTDs) are a group of congenital heart malformations that cause anomalies of cardiac outflow tracts. In the past few decades, many genes related to CTDs have been reported. Serum response factor (SRF) is a ubiquitous nuclear protein that acts as transcription factor, and SRF was found to be a critical factor in heart development and to be strongly expressed in the myocardium of the developing mouse and chicken hearts. The targeted inactivation of SRF during heart development leads to embryonic lethality and myocardial defects in mice. Methods To illustrate the relationship between SRF and human heart defects, we screened SRF mutations in 527 CTD patients, a cross sectional study. DNA was extracted from peripheral leukocyte cells for target sequencing. The mutations of SRF were detected and validated by Sanger sequencing. The affection of the mutations on wild-type protein was analyzed by in silico softwares. Western blot and real time PCR were used to analyze the changes of the expression of the mutant mRNA and protein. In addition, we carried out dual luciferase reporter assay to explore the transcriptional activity of the mutant SRF. Results Among the target sequencing results of 527 patients, two novel mutations (Mut1: c.821A > G p.G274D, the adenine(A) was mutated to guanine(G) at position 821 of the SRF gene coding sequences (CDS), lead to the Glycine(G) mutated to Asparticacid(D) at position 274 of the SRF protein amino acid sequences; Mut2: c.880G > T p.G294C, the guanine(G) was mutated to thymine (T) at position 880 of the SRF CDS, lead to the Glycine(G) mutated to Cysteine (C) at position 294 of the SRF protein amino acid sequences.) of SRF (NM_003131.4) were identified. Western blotting and real-time PCR showed that there were no obvious differences between the protein expression and mRNA transcription of mutants and wild-type SRF. A dual luciferase reporter assay showed that both SRF mutants (G274D and G294C) impaired SRF transcriptional activity at the SRF promoter and atrial natriuretic factor (ANF) promoter (p < 0.05), additionally, the mutants displayed reduced synergism with GATA4. Conclusion These results suggest that SRF-p.G274D and SRF-p.G294C may have potential pathogenic effects.